The Influence of Service Quality and Marketing Innovation Strategies of Gunung Limo Beverage Agents on Customer Satisfaction and Loyalty in Retail Stores - Digdo Haryanto; Heru Mulyanto (Pustaka Digital Indonesia, 2025)
The beverage industry is characterized by intense competition, driven by increasing consumer expectations for superior service quality and continuous marketing innovation. Gunung Limo, a beverage distribution agent, faces the strategic challenge of maintaining competitiveness and relevance in a dynamic retail environment. This study investigates the effect of Service Quality (X1) and Marketing Innovation Strategy (X2) on Customer Loyalty (Y), with Customer Satisfaction (Z) as a mediating variable. A quantitative research approach was employed, utilizing path analysis to assess direct and indirect relationships among the variables. Data were obtained from a structured questionnaire distributed to 100 respondents, comprising retail consumers and business partners affiliated with the Gunung Limo beverage agent. The findings reveal that both Service Quality and Marketing Innovation Strategy have a positive and significant impact on Customer Satisfaction. Furthermore, Customer Satisfaction is found to significantly mediate the relationship between the independent variables and Customer Loyalty. These results suggest that enhancing service standards and adopting innovative marketing approaches are critical for building customer satisfaction, which in turn fosters greater customer loyalty in the retail beverage segment. The study contributes to the understanding of strategic customer relationship management in the beverage distribution sector and offers practical insights for business actors seeki.